Soft Power through Steel and Strategy: Toyota’s Role in Indonesia–Japan Economic Diplomacy - Alya Diva Alfitrah; Lailatul Khoiriyah Romadhoni; Icha Ameylia Putri (Jurnal Mengkaji Indonesia, 2025)
Abstract: In an era of global economic interdependence, multinational corporations (MNCs) have become key players not only in investment and trade but also in shaping foreign policy and diplomatic relations. This article analyzes how Toyota Motor Corporation, a leading Japanese MNC, functions as a non-state actor in Indonesia’s foreign policy strategy, particularly within the framework of economic diplomacy. Purpose: This study investigates the strategic role of MNCs—focusing on Toyota—in influencing Indonesia’s foreign policy. It explores how Toyota contributes to bilateral relations, industrial policy, and Japan’s soft power strategy in Southeast Asia. Design/Methodology/Approach: The research adopts a qualitative, library-based method, drawing on academic literature, policy reports, and official documents. It builds a conceptual framework that connects corporate diplomacy with international political bargaining and national development. Findings: Toyota serves a dual function: as a major foreign investor and as a non-state diplomatic actor. Its activities—such as implementing the Domestic Component Level (TKDN) policy, enabling technology transfers, expanding exports, and facilitating workforce training—reinforce Indonesia’s industrial development while advancing Japan’s economic and geopolitical interests. The relationship between Toyota and the Indonesian state is reciprocal and strategic, involving continuous political and economic negotiations. However, the study also notes existing structural challenges, including unequal knowledge transfer and limited technological autonomy for domestic partners. Originality/value: This article offers a fresh lens by positioning MNCs as active agents in diplomacy and foreign policy. It bridges the gap between corporate international activity and traditional diplomatic studies, contributing to a deeper understanding of non-state actors in Global South foreign policy formation—particularly in the underexplored Indonesia–Japan context.